Early Sex Education and the Importance of Parents to Get Involved - Arifah Rasyidayanti; Luthfah Naily Faradisa; Tiara Diah Sosialita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Children who are supposed to get protection and feel safe during their developmental period are still at risk of becoming victims of sexual violence. Sex education in early childhood has an important role in reducing the risk of sexual violence. The main providers of sex education for children are parents. The subjects in this study were 60 parents of